2014
DOI: 10.1016/j.mayocp.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Phenotype-Based Genetic Test Prediction Score for Unrelated Patients With Hypertrophic Cardiomyopathy

Abstract: Objectives To determine the prevalence and spectrum of mutations and genotype phenotype relationships in the largest hypertrophic cardiomyopathy (HCM) cohort to date and provide an easy, clinically applicable phenotype-derived score that provides a pretest probability for a positive HCM genetic test. Patients and Methods Between 1999 and 2007, 1053 unrelated patients with the clinical diagnosis of HCM (60% male, age at diagnosis 44.4 ± 19 years) had HCM genetic testing for the HCM-associated myofilament gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
117
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 35 publications
(40 reference statements)
12
117
1
11
Order By: Relevance
“…Patients with VSB did not display a sex preference,1 14 15 in contrast to HCM, which has been generally characterised by a 3:2 male predominance,6 at least at younger ages 20 21. A recent review of 969 consecutive American and Italian patients with HCM demonstrated a reversed 60% versus 30% female predominance only in patients older than 60 years of age 22.…”
Section: Demographics and Medical Historymentioning
confidence: 85%
See 3 more Smart Citations
“…Patients with VSB did not display a sex preference,1 14 15 in contrast to HCM, which has been generally characterised by a 3:2 male predominance,6 at least at younger ages 20 21. A recent review of 969 consecutive American and Italian patients with HCM demonstrated a reversed 60% versus 30% female predominance only in patients older than 60 years of age 22.…”
Section: Demographics and Medical Historymentioning
confidence: 85%
“…Thus, a history of hypertension can no longer be considered tout court as an exclusion criterion for HCM when dealing with elderly patients. Indeed, in contemporary adult HCM populations, prevalence of hypertension ranges from 20% to 60% 20 21 23 25–29. The prevalence of hypertension in VSB observational studies ranges between 50% and 80%,1 14 15 thus slightly higher than that reported in HCM studies.…”
Section: Demographics and Medical Historymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are novel and informative by providing a reliable number (ie, 35%) 7 for the true yield and proportion of families that will have access to generational genetic screening should they choose this strategy over (or following) clinical screening with echocardiography and cardiovascular magnetic resonance (CMR) imaging. 4,8 This is a particularly important observation because too often the likelihood of successful genetic family screening has been cited as 50% to 70%, 1,2 a figure that includes variants of uncertain significance, which are usually sarcomere mutations not yet regarded as disease causing.…”
Section: Genetic Testingmentioning
confidence: 99%